Glucagon‐like peptide‐1 and vitamin D: anti‐inflammatory response in diabetic kidney disease in db/db mice and in cultured endothelial cells. Issue 8 (21st April 2016) - Einbinder, Yael; Ohana, Meital; Benchetrit, Sydney; Zehavi, Tania; Nacasch, Naomi; Bernheim, Jacques; Zitman‐Gal, Tali
Abstract: Background: Glucagon‐like peptide‐1 (GLP‐1) is a gut incretin hormone that stimulates insulin secretion and may affect the inflammatory pathways involved in diabetes mellitus. Calcitriol, an active form of vitamin D, plays an important role in renal, endothelial and cardiovascular protection. We evaluated the anti‐inflammatory and histologic effects of a GLP‐1 analogue (liraglutide) and of calcitriol in a db/db mouse diabetes model and in endothelial cells exposed to a diabetes‐like environment. Methods: Diabetic db/db mice were treated with liraglutide and calcitriol for 14 weeks, after which the kidneys were perfused and removed for mRNA and protein analysis and histology. Endothelial cells were stimulated with advanced glycation end products (AGEs), glucose, liraglutide and calcitriol. Total RNA and protein were extracted and analysed for the expression of selected inflammatory markers. Results: Typical histological changes, glomerular enlargement and mesangial expansion were seen in db/db mice compared with control mice. Glomerular hypertrophy was ameliorated with liraglutide, compared with db/db controls. Liraglutide up‐regulated endothelial nitric oxide synthase protein expression compared with the db/db control group and down‐regulated p65 protein expression. Calcitriol did not further improve the beneficial effect observed on protein expression. In endothelial cells, liraglutide treatment exhibited a dose‐dependent ability to prevent an inflammatory response in the selected markers: thioredoxin‐interacting protein, p65, IL6 and IL8. In most gene and protein expressions, addition of calcitriol did not enhance the effect of liraglutide. Conclusions: The GLP‐1 analogue liraglutide prevented the inflammatory response observed in endothelial cells exposed to a diabetes‐like environment and in db/db mice at the level of protein expression and significantly ameliorated the glomerular hypertrophy seen in the diabetic control group. Copyright © 2016 John Wiley & Sons, Ltd.